Draft Eighth Five Year Plan 1990-95 and Annual Plan 1991-92 Review and Outline Volume-I - Planning Commission (Planning Commission, 1990)
The economy of the State is agrarian in character. As many as 40.35% of the population in Census, 1981 were reported as workers against the national average of 33.4%. A look into the industrial classification of workers reveals that 63.60% of the workers were cultivators and 4.99% of the workers were agricultural labourers. 9.68% of the workers were found engaged in household industry, manufacturing, processing and repairs while the rest 21.73% were reported as other workers. The valley and a few pockets in the hills are cadastral surveyed; shifting cultivation is still prevalent in the hills. Rice is the main crop which accounts for about 86% of the total cropped area.
Planning Department